Megaworld United States - Brauch, Kevin (Stem curriculum series, 2011)
Take a closer look at how American scientists and engineers are leading the way in aviation, shipbuilding, and civil engineering. San Francisco's Bay Bridge is undergoing a safety upgrade that will see half the bridge demolished and replaced with the longest self-anchored suspension span in the world. Join the Air Force on an unusual rescue mission as they fly a zoo elephant from Alaska to retirement in California on board a C-17, the only aircraft big enough for the job, and much more.